PELAKSANAAN PELATIHAN KEWIRAUSAHAAN UNTUK MENINGKATKAN MINAT BERWIRAUSAHA SISWA SMKN 4 YOGYAKARTA - , Edy Sutrisno; , Prof. Dr. Abdul Halim, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Vocational High School should be able to create the entrepreneurs which can be able to create their own business for their life. But, in fact, there are some alumnus of SMK which have not worked yet after they graduate. It can be avoided if we grow their interest of business from the beginning, so that after they graduate, they can chose to be a entrepreneur instead of working in a company or continuing their study at the university. Based on the situation above, it is necessary to make some programs to increase the entrepreneurship intention of the student. One of the program which can increase the studentsâ entrepreneurship intention is the application of business management outside the teaching-learning activity inside the classroom. The program is called the Entrepreneurship Training. In SMKN 4 Yogyakarta, this kind of training has not been done before. So, the researcher here chose the Entrepreneurship Training Program. The objection of the research is to know if the Entrepreneurship Training Program can increase the business interest of the students of SMKN 4 Yogyakarta. If it can be proved, then the application of the Entrepreneurship Training Program can be one solution to overcome the low interest of the students in doing business. The research used the âQuasi Experimentâ method. There are two variables. They are dependent variable (the studentsâ interest) and independent variable (the application of the business management training). The experiment was done with the pre-test and post test design model. The subject of the research were the students of the X grade which were become the participants of the Entrepreneurship Training Program. There were 49 (forty nine) students. All of the participants were female. They came from 4 (four) different classes and different study program. They are from : class X of Beauty and Hair Do 2, class X of Boutique/Dressmaking 1, class X of Tours and Travel 2, class X of Foodmaking 2. In the training, the researcher was become the main facilitator, which guide the program and give the material of the training. The material given in the training was To Analyse the Market Opportunity and to Arrange the Business Plan. The application of the training is based on the PAKEM (Pembelajaran Aktif, Kreatif, Efektif, dan Menyenangkan / Active, Creative, Effective, and Fun Learning) teaching-learning concept and adopt some teaching-learning concept that the researcher has got from the TQI training (Teacher Quality Improvement) done by Titian Foundation in Yogyakarta. The result of the research shows that the objection of the program has been reached. The participants felt that they have got some benefits from this program. Then, with the statistic data prosess by software SPSS 17.0 for windows with the Paired Sample t Test analyse to the questioner result, the score of Sig (2-tailed) is 0,000. It means that the significant (p) < 0,05. So, the result of statistic test can answer the question of the researcher that the Entrepreneurship Training Program can increase the entrepreneurship intention of the students.